2009
DOI: 10.3164/jcbn.08-211
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Genistein and Daidzein in Affecting Lipid Metabolism in Rat Liver

Abstract: Summary Effects of soy isoflavones, genistein and daidzein, on the hepatic gene expression profile and indices for lipid metabolism were compared in rats. In the first experiment (Expt. 1), animals were fed diets containing 2 g/kg of either genistein or daidzein, or a control diet free of isoflavone for 14 days. In the second experiment (Expt. 2), rats were fed diets containing 1 or 2 g/kg of genistein, or an isoflavone-free diet for 16 days. Genistein at a dietary level of 2 g/kg reduced serum triacylglycerol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 24 publications
2
26
3
Order By: Relevance
“…This is supported by the evidence that the effects of GEN and DZN parallel those produced by the antioxidant SOD [see 6]. Thus, although other effects of GEN as a dietary compound inducing hormonal, metabolic and expression changes [55,56] cannot be ruled out, we maintain that its role as an antioxidant is crucial in accounting for these experimental findings. Accordingly, we first showed that these compounds can remove the extra ROS produced in cells undergoing apoptosis (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…This is supported by the evidence that the effects of GEN and DZN parallel those produced by the antioxidant SOD [see 6]. Thus, although other effects of GEN as a dietary compound inducing hormonal, metabolic and expression changes [55,56] cannot be ruled out, we maintain that its role as an antioxidant is crucial in accounting for these experimental findings. Accordingly, we first showed that these compounds can remove the extra ROS produced in cells undergoing apoptosis (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…Pancreatic cells showed the involvement of EGFR and the putative NFjB target EGR1 in the response to the phytoestrogen [193]. Similar effects have been shown in several others cellular systems [194][195][196] and in mice [197][198][199]. Genistein effects clearly depend on the dosage with pro-estrogenic activities being dominant at lower and anti-apoptotic activities at higher concentrations [200], similar observations have been reported by Konstantakopoulos et al [201].…”
Section: Anti-angiogenic Phytoestrogenssupporting
confidence: 73%
“…Genistein and daizein modulate the hepatic glucose and lipid-regulating enzyme activities. 4,5) Two meta-analyses have reported that the intake of soy protein and isoflavone reduced the levels of serum total cholesterol, LDL-cholesterol and triglycerides, and increased that of HDL-cholesterol. 6,7) The recently increasing use of soy food in diets has thus aroused a surge of interest in the potential physiological benefits.…”
mentioning
confidence: 99%